The turban pin aspiration syndrome: Awareness for a subtype of foreign body aspiration - Franziska Hainer; Wolfgang Klauß; Lutz Wünsch; Ludger Tüshaus (Elsevier, 2016)
The turban pin inhalation syndrome is known as a subtype of foreign body aspiration, mainly occurring in girls and young women wearing turbans. With the number of turban wearing girls and women increasing all over the world, attention must be brought to the risk associated with the use of hairpins. We present a case of metallic hairpin inhalation. In our case, the turban pin was successfully removed via rigid bronchoscopy.